Gender-based violence against men, a southeast Asian qualitative study - Sashini Jayaratne; Kumudu Wijewardena (SAGE Open Medicine)
Background and objectives: Gender-based violence is a major public health concern. Although, in many instances, violence against women and girls encompasses the entire spectrum of gender-based violence in the public eye, violence against men is a very real threat that is obscure and obliterated within cultural norms. Identification of the legal and cultural barriers men face is a very important step forward toward promoting gender equity. There is a severe paucity of research on gender-based violence against men in Sri Lanka. Methods: A qualitative study was conducted to explore the causes, effects, and help-seeking behaviors of men subjected to gender-based violence in the Colombo district, Sri Lanka. Two focus group discussions and two in-depth interviews were carried out among seventeen purposefully selected victims of gender-based violence and ten key informant interviews were carried out among service providers recruited purposefully in the Colombo district. Transcript analysis was done by using the thematic analysis method. Results: The study participants of the focus group discussions described themes of preconceived notions about the male sex, gender bias, power play, and masculinity norms as causes leading to gender-based violence. Many participants described their own or a peer’s life experience to explain the experiences and consequences of gender-based violence. The key informant interview revealed certain aspects of the support systems which need revision in order to make the services more accessible to men. Conclusion: This study provides evidence regarding the hitherto undiscussed topic of gender-based violence against men in Sri Lanka. The findings highlight the importance of taking into consideration and inclusion of men in the development of policies for gender-based violence in Sri Lanka.